Epitope mapping of the N‐terminal portion of tissue transglutaminase protein antigen to identify linear epitopes in celiac disease. (15th May 2014) - Di Pisa, Margherita; Buccato, Patrick; Sabatino, Giuseppina; Real Fernández, Feliciana; Berti, Brunilde; Cocola, Francesco; Papini, Anna Maria; Rovero, Paolo
<x xml:space="preserve">Abstract</x> Celiac disease (CD) is an autoimmune mediated disease with complex and multifactorial etiology. Gluten intake triggers a composite immune response involving T‐cells and B‐cells and leading to the secretion of autoantibodies if a genetic predisposition is present. Untreated CD patients show high levels of circulating autoantibodies directed to different auto‐antigens present in the intestinal mucosa. The most important auto‐antigen is the endomysial enzyme tissue transglutaminase (tTG). Both IgA and IgG antibody isotypes to tTG are known, but only the IgA antibodies demonstrate the highest disease specificity and thus are considered disease biomarkers. Because the pathogenicity and exact tTG binding properties of these autoantibodies are still unclear, the characterization of tTG antigenic domains is a crucial step in understanding CD onset and the autoimmune pathogenesis. Overlapping peptide libraries can be used for epitope mapping of selected protein portions to determine antigenic fragments contributing to the immunological activity and possibly develop innovative peptide‐based tools with high specificity and sensitivity for CD. We performed an epitope mapping study to characterize putative linear auto‐antigenic epitopes present in the tTG N‐terminal portion (1–230). A library of 23 overlapping peptides spanning tTG(1–230) was generated by Fmoc/tBu solid‐phase peptide synthesis and screened by immunoenzymatic assays employing patients' sera. The results indicate that four synthetic peptides, that is, Ac‐tTG(1–15)‐NH2, Ac‐tTG(41–55)‐NH2, Ac‐tTG(51–65)‐NH2, and Ac‐tTG(151–165)‐NH2, are recognized by IgA autoantibodies circulating in CD patients' sera. These results offer important insight on the nature of the antigen‐antibody interaction. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.